Breakthrough : Catalyst - Book 3 - Grumley, Michael C. ([United States] : [Michael C. Grumley], 2015)
In 1984 a doomsday vault was constructed on a remote island in the Arctic Ocean. Its purpose was to preserve Earths genetic history in the event of a global catastrophe. Now, decades later, a second vault has been uncovered. This one resting where no one ever expected. And the problem is ... its not ours. Yet even more curious than the vault itself, is what lies inside. Seeds. Millions of seeds. Each with a genetic embryo untouched and perfectly preserved. Waiting. No one knows who built it. Or when. What we have managed to figure out is that whoever it was traveled an immense distance. For the sole purpose of hiding their genetic blueprints on Earth. But why? Now a small group of marine biologists and navy investigators have been assigned to find out. Before anyone else does. But Alison Shaw and John Clay are not prepared for what they are about to uncover. Beginning with the truth behind our own evolution.
Keywords: Marine biologists -- Fiction; Women marine biologists -- Fiction; Discoveries in science -- Fiction; Science fiction; Thrillers (Fiction); Action and adventure fiction